How to Engage with Younger Users on Instagram: A Comparative Analysis of HBO and Netflix in the Spanish and US Markets. Issue 2 (3rd April 2019) - Martín-Quevedo, Juan; Fernández-Gómez, Erika; Segado-Boj, Francisco
ABSTRACT: Social media have become useful tools for audiovisual promotion, especially to reach niche audiences. Twitter promotional strategies have been widely studied, yet other growing platforms such as Instagram have been less analyzed. This paper examines the Instagram promotional strategies of two pay-per-view platforms (HBO and Netflix) in two markets (the USA and Spain). A total of 731 messages, posted between May and November 2017, were analyzed to identify their formal features, objectives, and their content's emotional and cognitive elements posted on HBO and Netflix's Spanish and US accounts. The results showed acute differences between how HBO and Netflix use their Instagram accounts in the two markets (Spain and the USA). The Spanish accounts mostly provided information, while the US accounts both provided information and promoted program content. Posts from US accounts more frequently included links to social media, particularly to celebrity accounts. Spanish accounts relied more on diegetic images, whereas US accounts emphasized non-diegetic and off-set images. Netflix used humor more than HBO did, and a stronger focus on celebrities. Humor and positive tone were found to be linked to higher engagement.